Applying Research Syntheses to Networked Learning Research – Help or Hinderance for Collective Knowledge Creation? - Bedenlier, Svenja; Buntins, Katja (Proceedings of the International Conference on Networked Learning, 2026)
The suggested roundtable aligns with the thematic focus of the conference on research designs/ research methods and responsible research, and is envisaged to foster critical dialogue amongst participants who want to engage or are engaged with the approach of research syntheses in networked learning research.